(untitled) (Research, Society and Development, 2022)
It aimed to compare the profile of knowledge about HMI between pediatric dentists and general practitioners. This was a cross-sectional study, with the application of questionnaires to 40 dentists duly registered with the Regional Council of Dentistry of Paraíba (CRO-PB), being 20 general practitioners and 20 specialists in pediatric dentistry. Most of the participants in this research were women (n=36; 90.0%), with an average age of 32.45 years (+7.62) and professional experience over 11 years. The two groups evaluated obtained satisfactory theoretical knowledge in relation to etiological factors, especially the genetic factor. Regarding the clinical characteristics, most responded that it affects enamel and dentin, with demarcated opacities, diffuse, with asymmetric location and that affects some teeth. Both groups presented theoretical knowledge, however, the evaluation of images showed a difference between the two groups. Regarding clinical management, both groups indicated the use of sealants, fluortherapy and restoration in glass ionomer cement, with no significant difference (p>0.05). Pediatric dentists correctly identified images with HMI (n=13; 65.0%), while general practitioners considered the same image as enamel hypoplasia (n=11; 55.0%). Pediatric dentists have a greater mastery of HMI in relation to diagnosis, but knowledge about etiology, treatment and choice of material did not show a statistically significant difference between the groups (p>0.05). It is concluded that the profile of knowledge about etiology, treatment and clinical characteristics between both groups present similar levels of knowledge. When evaluating clinical images, pediatric dentists showed a correct response pattern, unlike general practitioners.